Physical activity and physical fitness of the Lubelski Third Age Univeristy students in their opinion - Książek, Piotr; Staniak, Justyna; Szczepanik, Natalia; Kamiński, Maciej; Okoński, Piotr (Polish Journal of Public Health, 2013)
Introduction. The increasing number of older people determines the necessity to activate them socially and physically. Research should be carried out to find if this particular social group leads a healthy lifestyle. Physical activity is one of its determinants and it influences maintaining good physical and psychical form.Aim. The aim of this survey was to present subjective physical activity level of the students of the Third Age University in Lublin.Material and methods. The study was conducted at the Third Age University in Lublin among 85 students aged above 55 years. The students were examined with a questionnaire.Results. Most of the students of the Lubelski Third Age University are active people. Fifty per cent of respondents exercise at university classes. Among active people, 80% exercise also at home. Mostly preferred form of activity is gymnastics (31%). It was also indicated that age can influence the opinion about personal health state. The biggest group of respondent (40%) evaluating it as good were 55-64 year-old students. However, the oldest age group (75-84 years old) is most satisfied of their physical form.Conclusions. The students of the Lubelski Third Age University are physically active. The students can maintain their fitness thanks to a wide offer of the university, which is the health-favoring environment and which can help with learning pro-health habits.